The constitution of collaborative learning environments in continuing education actions: Experimental approach with GeoGebra - Zampieri, Maria Teresa [UNESP]; Javaroni, Sueli Liberatti [UNESP] (FapUNIFESP (SciELO), 2018)
The aim of this article is to discuss two actions of continuing education, and how they constituted themselves in collaborative learning environments. These actions focused on the accomplishment of experimental activities withtheGeoGebra software, in which researchers and teachers of Basic Education Mathematics participated. In addition, some empirical data are presented and discussed here, in order to elucidate the discussions about two of these activities. These actions of continuing education compose the research scenario of a qualitative doctoral research that is under development, linked to a thematic project of large scale that has been carried out within the Research Group in Informatics, Other Media and Mathematics Education(GPIMEM). One of the actions happened in the city of Bauru/SP, and the other in the city of Coimbra, Portugal. The activities addressed in these actions, as well as those developed in the group's other research projects, generally have a theoretical-methodological approach of an experimental nature. It is concluded that teachers, while performing such activities and opining about other mathematical contents that could have been contemplated in them, studied the software functionalities, criticizing the proposed approaches, culminating in suggestions of adaptations, making them viable to be applied in their respective classrooms. Finally, it is evident that participation in such actions enabled them to glimpse ways to create collaborative learning environments in their respective work contexts.
A Constituição de Ambientes Colaborativos de Aprendizagem em Ações de Formação Continuada: abordagem experimental com GeoGebra
Keywords: Digital Technologies; Mathematics Education; Teaching and Learning of Mathematical Contents